Bioaccessibility and stability of β-carotene encapsulated in plant-based emulsions: impact of emulsifier type and tannic acid. Issue 11 (16th October 2019) - Li, Ruyi; Tan, Yunbing; Dai, Taotao; Zhang, Ruojie; Fu, Guiming; Wan, Yin; Liu, Chengmei; McClements, David Julian
Abstract : The effect of two plant-based emulsifiers (quillaja saponin, QS and gum arabic, GA) and a polyphenol (tannic acid) on the formation, stability, digestibility, and β-carotene (BC) bioaccessibility of flaxseed oil-in-water emulsions was investigated. Abstract : The effect of two plant-based emulsifiers (quillaja saponin, QS and gum arabic, GA) and a polyphenol (tannic acid) on the formation, stability, digestibility, and β-carotene (BC) bioaccessibility of flaxseed oil-in-water emulsions was investigated. The gastrointestinal behavior of the emulsions was studied using a simulated gastrointestinal tract (GIT) consisting of mouth, stomach, and small intestine regions. In the absence of tannic acid, the initial extent of lipid digestion depended strongly on emulsifier type, with 45% and 76% of the free fatty acids being released after 5 min digestion for QS- and GA-emulsions, respectively. Even so, the lipid droplets were completely digested in both emulsions after 2 h incubation in the small intestine phase. Tannic acid addition (0.01% and 0.1% w/w) slowed down lipid digestion, but did not impact the final extent. The droplets in the QS-emulsions containing 0.1% tannic acid were highly flocculated in the stomach phase. Molecular docking simulations indicated that the interactions between tannic acid and the saponins were mainly driven by hydrogen bonding and hydrophobic interactions. Moreover, they showed that the interactions between tannic acid and QS were stronger at pH 2.5 than at pH 7.0, which would account for the extensive droplet flocculation observed under acidic conditions in the stomach. Emulsifier type and tannic acid addition had no significant influence on BC bioaccessibility. The GA-emulsions exhibited better stability than the QS-emulsions when stored at elevated temperatures (55 °C for 7 days). Tannic acid addition effectively inhibited temperature-induced BC degradation. These results may facilitate the design of more efficacious nutraceutical-loaded functional foods and beverages.